Odpowiedzi

2009-12-19T15:43:30+01:00
A) -(-(-(-5))) + (-4) * (8-12) - (-(-3)) * (-12) : (-(-6))=
=5+16-(-36:6)=21+6=27

B) -[-(-10+17) - 8 ] : [ -4 + 3 * (-5) * (-2) : 10 - 2 ] + (-7) =
=15:(-4+3-2)-7=15:(-3)-7=-5-7=-12

:)
1 5 1
  • Użytkownik Zadane
2009-12-19T15:44:23+01:00
A) -(-(-(-5))) + (-4) * (8-12) - (-(-3)) * (-12) : (-(-6)) = 5-32+48+36:6=57/6=9,5

-[-(-10+17) - 8 ] : [ -4 + 3 * (-5) * (-2) : 10 - 2 ] + (-7) =-(-7):(-4+30:10-2)=7:_2=-3,5
1 5 1
Najlepsza Odpowiedź!
2009-12-19T15:48:38+01:00
A.
-(-(-(-5))) + (-4) * (8-12) - (-(-3)) * (-12) : (-(-6)) =
5 + (-4)*(-4) - (3)*(-12):(6) =
5 + 16 - (-36):(6) =
5 + 16 - (-6) =
5 + 16 + 6 =
27

B.
-[-(-10+17) - 8 ] : [ -4 + 3 * (-5) * (-2) : 10 - 2 ] + (-7) =
-[-(7) - 8] : [-4 + (-15) * (-2) : 10 - 2] + (-7) =
-[-15] : [-4 + 30 : 10 -2] + (-7) =
15 : [-4 + 3 - 2] + (-7) =
15 : [-3] + (-7) =
(-5) + (-7) =
-12
1 5 1